The photograph - Lewis, Beverly, 1949- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2015)
"In a 1980s Amish community, three sisters face a time of transition in their family, and each searches for a way to define her own future"--
Keywords: Amish -- Fiction; Sisters -- Fiction